DOI: 10.32469/10355/78090
|View full text |Cite
|
Sign up to set email alerts
|

Transformative technology : examining the capacity of virtual reality induced awe to change self-transcendent values and improve hedonic and eudaimonic well-being

Abstract: Awe is an emotion that tends to shift focus away from individual concerns of the self towards collective interests that transcend the self. The primary purpose of the current study was to examine whether an experimentally induced experience of awe, compared to amusement, had the potential to change participant's self-transcendent values of universalism (e.g., preserving nature and a world at peace) and benevolence (e.g., honesty and concern for the welfare of others). The secondary purpose was to examine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…It has been found that awe elicited via VR is useful for mood induction and prosocial behavior as well (Kahn & Cargile, 2021). It was also found that awe elicited by VR results in both hedonic and eudaimonic well-being (Pratscher, 2020). With its power of enhancing presence and emotion, VR has the potential for amplifying the experiences of eudaimonia.…”
Section: Eudaimonia In Games and Vrmentioning
confidence: 99%
“…It has been found that awe elicited via VR is useful for mood induction and prosocial behavior as well (Kahn & Cargile, 2021). It was also found that awe elicited by VR results in both hedonic and eudaimonic well-being (Pratscher, 2020). With its power of enhancing presence and emotion, VR has the potential for amplifying the experiences of eudaimonia.…”
Section: Eudaimonia In Games and Vrmentioning
confidence: 99%